The Affidavit of Support Legally Enforceable for Foreign Citizens in Indonesia - Ziad Abdullah (Notary Master Programe, Faculty of Law Universitas Jenderal Soedirman, 2022)
This study aims to assess authorize of a notary in making affidavit deeds regard to inheritance rights for foreign citizens. Focus this study to discuss the application affidavit as evidence in court based on the dispute case of Chung Jung as a foreign citizen who demands his rights as heirs. The purpose of the discussion is to answer the problem that Indonesia has not specifically regulated affidavits which used to evidence in court. This study using the statute approach and case approach to investigate the regulations and the case related to the issues discussed. As a result, the affidavit deed made by the Indonesian Notary does not have the power to resolve dispute, it is used as complementary evidence. Claims using affidavit deed as single evidence have no legal strength power in court.Keywords: Affidavit; Authentic Deed; Notary; Civil Cases; Foreign Citizens